(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Determination of sex from the skeletal remains is of immense importance in the field of forensic medicine, physical anthropometry and anthropology. Exact determination of sex from skeleton has been a critical issue in medico-legal cases and the accuracy depends on the type of material available and methods applied. Various previous studies have demonstrated sternum as an important tool for the determination of sex in the mutilated, fragmented bodies and in advance stage of decomposition. Sternum is a bone which is easily retrievable even from the advance decomposed body and also from the bundle of bone. Total 632 subjects, there were 350 male and 282 female with the age >25 years, were taken for the study and data analysis was done by using SPSS software and relevant statistical test was applied. In our study, bisexual variation in relation to width of S3 segment of mesosternum was found conclusive.